THE METHODOGICAL ROLE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING ENGLISH ACADEMIC WRITING SKILLS - O’roqova Ruhshona Shahriyor qizi (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study explores the methodogical role of artificial intelligence(AI) in developing English academic writing skills among English as a Foreign language (EFL) learners. In recent years, AI-based digital tools have increasingly entered the educational process, creating new opportunities to enhance students’ writing performance. The aim of this article is to analyze how AI technologies contribute to organizing ideas, improving coherence and cohesion, expanding academic vocabulary, and reducing grammatical errors in academic writing.